A new species of Habenaria (Orchidaceae) from the Western Ghats, India. Issue 1 (2nd January 2019) - Prasad, Kothareddy
ABSTRACT: Habenaria keralensis (Orchidaceae), a new species from the Agasthyakoodam in Southern Western Ghats of Kerala (India) is described and illustrated. It differs from Habenaria dolichostachya by plants 25–35 cm high, leaves ovate-lanceolate, ovary pedicelled, floral bracts shorter than the ovary, elliptic-acuminate, lip as long as the sepals, lobes subequal.